2020
DOI: 10.3390/v12040368
|View full text |Cite
|
Sign up to set email alerts
|

Rabies in the African Civet: An Incidental Host for Lyssaviruses?

Abstract: In South Africa, canid rabies virus (RABV) infection is maintained in domestic and wildlife species. The identification of rabies in African civets raised the question of whether this wildlife carnivore is a potential reservoir host of RABVs of direct and ancestral dog origin (dog-maintained and dog-derived origins) with an independent cycle of transmission. Genetic analyses of African civet nucleoprotein sequences for 23 African civet RABVs and historically published sequences demonstrated that RABVs from Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…For example, the canine parvoviruses were reported to cause diarrhea and deaths in civets and the viral DNA can be detected in the brain, liver, heart, spleen and small intestine 3 , which is consistent with the wide distribution of its receptor TFRC in the civet organs. Lyssaviruses usually cause fatal encephalitic diseases in a wide range of mammals with civet infections reported in Africa and Asia 5,6 . Our results showed an obvious enrichment of a related receptor, NCAM1 , in multiple cell types of the civet frontal lobe, which may contribute to the neurovirulence of these viruses.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the canine parvoviruses were reported to cause diarrhea and deaths in civets and the viral DNA can be detected in the brain, liver, heart, spleen and small intestine 3 , which is consistent with the wide distribution of its receptor TFRC in the civet organs. Lyssaviruses usually cause fatal encephalitic diseases in a wide range of mammals with civet infections reported in Africa and Asia 5,6 . Our results showed an obvious enrichment of a related receptor, NCAM1 , in multiple cell types of the civet frontal lobe, which may contribute to the neurovirulence of these viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Clade C indicated that there was genetic homology between the RABV sequences collected from civet species in the western parts of Zimbabwe, jackal species in the southern parts of Botswana, and a genet in the northern parts of the NW Province. During a previous investigation of the molecular epidemiology of rabies in Zimbabwe, the researchers found strong evidence that a sylvatic cycle of rabies was being maintained by the civet populations in Zimbabwe [33]. During that study, the authors noted that the RABV cycle within the civet populations was related to an outbreak of mongoose rabies circulating within the slender mongoose (Galerella sanguinea) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, rabies has become an increasing concern in the NW province of South Africa, given the apparent expanding involvement of wildlife in the country [9,14,33]. However, very little is known about the epidemiological drivers nor the interplay between dog and wildlife rabies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RABV circulation in wildlife not only poses a significant threat for conservation of endangered mammals but also a latent risk for the re-establishment of rabies’ cycles in unvaccinated domestic animals, which renders rabies as an authentic priority health concern [ 13 , 14 , 15 , 16 ]. Based on a literature review, rabies is reported in about 200 mammals, and of those, sixteen are classified as endangered [ 17 ].…”
Section: Patching the Way For Appropriate Epidemiology Of Multi-host ...mentioning
confidence: 99%